2016
DOI: 10.1002/2015jd024153
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of materials internally mixed with black carbon measured in Tokyo

Abstract: Black carbon (BC) aerosols become internally mixed with non‐BC compounds (BC coatings) during aging in the atmosphere. In this study, we measured the hygroscopicity parameter κ on a single‐particle basis for both BC‐coating materials (κBC‐coat) and BC‐free particles (κBC‐free) in the urban atmosphere of Tokyo, using a single‐particle soot photometer (SP2). In our measurement system, dry ambient particles were first mass selected by an aerosol particle mass analyzer, then humidified, and then passed to the SP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…The number fractions of dust‐like FeO x particles to all of the FeO x particles with D m = 170–270 nm reached 25% during this period (Figure S6a), whereas, in other periods, they were generally 5% in Tokyo (Figure ). The median log( C s‐be / C s‐oi ) value for BC with D m = 200 nm reached 0.7 (Figure S6b), which corresponds to a coating thickness of ~100 nm under an assumed core‐shell structure for BC‐containing particles (Ohata et al, ). This coating thickness for BC is much larger than the typical coating thickness (~10 nm) observed during the other periods in Tokyo.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The number fractions of dust‐like FeO x particles to all of the FeO x particles with D m = 170–270 nm reached 25% during this period (Figure S6a), whereas, in other periods, they were generally 5% in Tokyo (Figure ). The median log( C s‐be / C s‐oi ) value for BC with D m = 200 nm reached 0.7 (Figure S6b), which corresponds to a coating thickness of ~100 nm under an assumed core‐shell structure for BC‐containing particles (Ohata et al, ). This coating thickness for BC is much larger than the typical coating thickness (~10 nm) observed during the other periods in Tokyo.…”
Section: Resultsmentioning
confidence: 96%
“…The observation periods in Tokyo spanned 20 days in July and August 2014 and 16 days in February 2014; for simplicity, we refer to these periods as “summer” and “winter,” respectively. The observations in the summer were conducted as a Black Carbon/Carbonaceous Aerosol Removal Experiment in Tokyo (BC‐CARE Tokyo) field campaign, which was discussed in our previous study (Ohata et al, ). The observation period in Chiba spanned 21 days in September 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Coating thickness is calculated from the measured optical size using Mie theory, assuming a spherical core-shell morphology. Ohata et al [2016] recently evaluated the accuracy of this method using mass-selected internal mixtures of laboratory aerosol. They found that the SP2 Journal of Geophysical Research: Atmospheres 10.1002/2016JD025688 scattering estimate of coating thickness agreed with that calculated from the difference between the total particle mass and the BC core mass to within 10% for particles with a total diameter at least 1.5 times the diameter of the core (i.e., thickly coated particles).…”
Section: Bc Aerosol Methodsmentioning
confidence: 99%
“…At the remote site of Hedo (26.9°N, 128.3°E) on Okinawa Island, Japan, the contribution was about 8% in spring 2016 (section A4, Figure a). BC particles become more active as cloud condensation nuclei as their diameters increase, and larger BC particles have been observed to be removed more efficiently by wet deposition than BC particles with smaller diameters [ Ohata et al , ; Moteki et al ., ; Kondo et al , ]. BC particles larger than 1 µm should be scavenged more efficiently during long‐range transport to the Arctic from lower latitudes.…”
Section: Comparisons Of Mbc (Cosmos) With Mec Measurements At Barrow mentioning
confidence: 99%